2015
DOI: 10.7205/milmed-d-14-00101
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Cross-Sectional Study Comparing Depression and Health Service Deficits Between Rural and Nonrural U.S. Military Veterans

Abstract: With involvement in two wars over the past decade, there has been a documented increase in depression prevalence and suicide incidence among U.S. military veterans. Because higher proportions of veterans come from rural communities, access to care may be an issue when behavioral health care is needed. Although the Veterans Administration has expanded health services in rural areas, this has not always resulted in increased service utilization. This study examined the prevalence of depression and associated hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…For example, veterans are more likely to have chronic pain and long-term health conditions requiring polypharmacy (Im et al, 2015), conferring both additional suicide risk and increased access to suicide means. Veterans are also more likely to be socially isolated and use alcohol and drugs in contexts where an overdose may not be detected (Dittrich et al, 2015). Illicit drugs and alcohol might be used very socially in the military setting, and service members may have fewer opportunities to overdose without being discovered by others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, veterans are more likely to have chronic pain and long-term health conditions requiring polypharmacy (Im et al, 2015), conferring both additional suicide risk and increased access to suicide means. Veterans are also more likely to be socially isolated and use alcohol and drugs in contexts where an overdose may not be detected (Dittrich et al, 2015). Illicit drugs and alcohol might be used very socially in the military setting, and service members may have fewer opportunities to overdose without being discovered by others.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority (n = 25) of included studies were cross‐sectional designs, 3,20–43 followed by noncomparative qualitative study designs 44–48 (n = 5), 3 cohort studies (n = 2 retrospective cohort 49,50 ; n = 1 nonconcurrent cohort 51 ), and 1 case‐control 52 study (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Rural individuals with substance abuse history were twice as likely to die by suicide (OR = 2.3, 95% CI: 1.0‐5.3) 21 . Other individual level factors identified included past suicide exposure, 20,24 behavioral health care use, 20,24,33 financial difficulties, 20,21,24,48 and attitudinal barriers to care 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study [ 4 ], analyzing Behavioral Risk Factor Surveillance System (BRFSS) data, examined depression and HSDs in rural compared to non-rural adult populations and found that rural residency was an independent risk factor for greater HSDs in adults with depression. [ 8 ] In 2014, a study was published examining the prevalence of HSDs in depressed (determined by a standardized and validated measure) US veterans [ 11 ]. Rural residency was found to be an independent risk factor for greater odds of having a HSD in rural veterans.…”
Section: Introductionmentioning
confidence: 99%